The Influence of Trust and Service Quality on Loyalty trought Satisfaction as Mediator for BRImo Users - Adinda Putri Kusuma Dewi; Ignatia Martha Hendrati; Wiwik Handayani (Management Analysis Journal, 2024)
This study aims to ascertain how loyalty among BRImo mobile banking users in Sidoarjo is impacted by customer satisfaction and trust. The study looks at how customer satisfaction and trust affect loyalty among BRImo mobile banking users in Sidoarjo. In this study, 121 BRImo mobile banking users were chosen as a sample utilizing the random sampling technique. This study employs a quantitative approach, with primary data obtained from surveys that were given to participants. The Smart-PLS program uses multiple linear regression for data processing and analysis. The study's findings demonstrate that, both directly and indirectly, the service quality variable significantly and favorably affects loyalty among Sidoarjo's BRImo mobile banking customers. Loyalty among BRImo mobile banking users is not positively and significantly impacted by trust. However, among Sidoarjo's BRImo mobile banking users, The construct of trust exerts a beneficial and discernible influence on loyalty, operating through the conduit of satisfaction. This research provides a foundation for further research on customer loyalty in the financial technology sector and highlights the importance of an integrated approach to customer satisfaction, trust, and service quality.